Magnetic resonance imaging and clinical findings in seminal vesicle pathologies - Zafer Ozmen; Fatma Aktas; Nihat Uluocak; Eda Albayrak; Ayşegül Altunkaş; Fatih Çelikyay (International Brazilian Journal of Urology)
ABSTRACT Purpose Congenital and acquired pathologies of the seminal vesicles (SV) are rare diseases. The diagnosis of SV anomalies is frequently delayed or wrong due to the rarity of these diseases and the lack of adequate evaluation of SV pathology. For this reason, we aimed to comprehensively evaluate SV pathologies and accompanying genitourinary system abnormalities. Materials and Methods Between March 2012 and December 2015, 1455 male patients with different provisional diagnosis underwent MRI. Congenital and acquired pathology of the SV was identified in 42 of these patients. The patients were categorized according to their SV pathologies. The patients were analyzed in terms of genitourinary system findings associated with SV pathologies. Results SV pathologies were accompanied by other genitourinary system findings. Congenital SV pathologies were bilateral or predominantly in the left SV. Patients with bilateral SV hypoplasia were diagnosed at an earlier age compared to patients with unilateral SV agenesis. There was a significant association between abnormal signal intensity in the SV and benign prostate hypertrophy (BPH) and patient age. Conclusion SV pathologies are rare diseases of the genitourinary system. The association between seminal vesicle pathology and other genitourinary system diseases requires complete genitourinary system evaluation that includes the seminal vesicles.